PROTOCOL: Instruments for the evaluation of emotional intelligence in persons with hearing impairments: A scoping review - Petra Potmesilova; Milon Potmesil; Jana Mareckova (Campbell Systematic Reviews, 2022)
Abstract Objective This scoping review aims to identify and describe the instruments used to evaluate emotional intelligence in deaf and hard of hearing (D/HH) persons. Introduction Emotional intelligence is a person's ability to work with emotions in response to a particular situation. Deafness or a hard of hearing has a negative effect on functioning in the field of emotional intelligence and leads to a specific approach to the diagnosis or evaluation of emotional intelligence. Inclusion Criteria The scoping review will consider studies focused on persons who are deaf or hard of hearing at any age. The review will consider studies that feature existing instruments and the process of the evaluation of emotional intelligence in people with hearing disabilities. Relevant information will include the type, extent, and form of possible modification of specific instruments and approaches. Criteria for the exclusion of the study will be in terms of the target category being persons with a cochlear implant, psychiatric diagnoses, persons who have become deaf, and persons with multiple disabilities. Methods The review will be conducted following the JBI methodology for scoping reviews. The databases to be searched include MEDLINE, Embase, CINAHL Plus, ProQuest Central, PsycINFO, Scopus, Web of Science, Clinical Trials, and the Cochrane Central Register of Controlled Trials (CENTRAL), and Google Scholar. The search for unpublished studies will include ProQuest Dissertations and Theses (ProQuest). Eligible studies will undergo data extraction by two independent reviewers using a tool created by the authors. Along with a narrative summary, the results will be presented in diagrammatic or tabular form.